Metformin versus metformin plus pioglitazone on gonadal and metabolic profiles in normal-weight women with polycystic ovary syndrome: a single-center, open-labeled prospective randomized controlled trial - Han Zhao; Jiaqi Zhang; Chuan Xing; Xiangyi Cheng; Bing He (BMC, 2024)
Abstract Objective To investigate the effects of metformin (MET) monotherapy and pioglitazone plus MET (PIOMET) therapy on gonadal and metabolic profiles in normal-weight women with polycystic ovary syndrome (PCOS). Methods Sixty normal-weight women with PCOS were recruited between January and September 2022 at the Shengjing Hospital of China Medical University. They were randomly assigned to the MET or PIOMET groups for 12 weeks of MET monotherapy or PIOMET therapy. Anthropometric measurements, menstrual cycle changes, gonadal profiles, and the oral glucose insulin-releasing test (OGIRT) were performed at baseline and after the 12-week treatment. Results Thirty-six participants completed the trial. MET and PIOMET therapies improved menstrual cycles after the 4- and 12-week treatments; however, there was no statistical difference between the two groups. PIOMET therapy improved luteinizing hormone (LH), luteinizing hormone/follicle stimulating hormone (LH/FSH) ratio, and free androgen index (FAI) levels after the 4-week treatment, whereas MET monotherapy only improved total testosterone (TT) levels compared to baseline (P < 0.05). Both MET and PIOMET therapies improved TT and anti-Mullerian hormone (AMH) levels after the 12-week treatment (P < 0.05). In addition, only PIOMET therapy significantly improved sex hormone-binding globulin (SHBG), FAI, and androstenedione (AND) levels than the baseline (P < 0.05). PIOMET therapy improved SHBG and AMH levels more effectively than MET monotherapy (P < 0.05). Furthermore, PIOMET treatment was more effective in improving blood glucose levels at 120 and 180 min of OGIRT compared to MET monotherapy (P < 0.05). Conclusions In normal-weight women with PCOS, PIOMET treatment may have more benefits in improving SHBG, AMH, and postprandial glucose levels than MET monotherapy, and did not affect weight. However, the study findings need to be confirmed in PCOS study populations with larger sample sizes.